2002
DOI: 10.1152/japplphysiol.00644.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gravity on chest wall mechanics

Abstract: Chest wall mechanics was studied in four subjects on changing gravity in the craniocaudal direction (G(z)) during parabolic flights. The thorax appears very compliant at 0 G(z): its recoil changes only from -2 to 2 cmH(2)O in the volume range of 30-70% vital capacity (VC). Increasing G(z) from 0 to 1 and 1.8 G(z) progressively shifted the volume-pressure curve of the chest wall to the left and also caused a fivefold exponential decrease in compliance. For lung volume<30% VC, gravity has an inspiratory effect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 17 publications
3
19
0
Order By: Relevance
“…The relatively small effect on the rib cage is also consistent with the relatively small changes in in oesophageal pressure seen in seated subjects in parabolic flight [26]. The studies in parabolic flight had the advantage of measurements both in micro-and hypergravity, and these showed significant nonlinearity in chest wall behaviour [27,28], emphasising the inability to adequately predict the situation in microgravity by extrapolation from hypergravity.…”
Section: Lung Volumes and Expiratory Flowsmentioning
confidence: 55%
“…The relatively small effect on the rib cage is also consistent with the relatively small changes in in oesophageal pressure seen in seated subjects in parabolic flight [26]. The studies in parabolic flight had the advantage of measurements both in micro-and hypergravity, and these showed significant nonlinearity in chest wall behaviour [27,28], emphasising the inability to adequately predict the situation in microgravity by extrapolation from hypergravity.…”
Section: Lung Volumes and Expiratory Flowsmentioning
confidence: 55%
“…During quiet breathing, the loops begin at the intersection between the lung and chest wall volume-pressure curves, namely FRC, which corresponds to the mechanical resting point of the respiratory system. For these same subjects, previous studies (5,6) showed that a change in gravity and posture induced a change in the mechanical properties of both lung and chest wall and, consequently, a displacement of FRC.…”
Section: Methodsmentioning
confidence: 90%
“…The subjects had previous parabolic flight experience, were trained to perform the respiratory maneuvers, and were well accustomed to abrupt changes in G z, which could occur several times during each flight. This same subject set had previously performed studies on how changes in G z affect chest wall and lung mechanics (5,6). Subjects gave their informed consent, and the protocol was approved by a review board.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations